Stevens' Handbook of Experimental Psychology and Cognitive Neuroscience 2018
DOI: 10.1002/9781119170174.epcn303
|View full text |Cite
|
Sign up to set email alerts
|

Word Processing

Abstract: This chapter reviews theories and empirical research on how humans retrieve meaning from speech or text. We first review research concerning how word meanings are represented. Here theories are divided between embodiment accounts proposing that word meanings are grounded in sensorimotor systems, and distributional semantics accounts proposing that meanings can be viewed as inter‐word distributional relations. We argue that these two approaches deal with different aspects of word meanings and should be integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 168 publications
0
8
0
Order By: Relevance
“…They automatically converge on lexical choices during object naming tasks (e.g., whether to use couch or sofa to name a piece of furniture; Brennan & Clark, 1996; Clark & Wilkes-Gibbs, 1986). They are also found to repeat each other’s syntactic structure (e.g., actives vs. passives) when they take turns to describe depicted events (Branigan, Pickering, & Cleland, 2000; Cai, Pickering, & Branigan, 2012). Some other forms of alignment may reflect more strategic efforts to take a shared perspective with a conversational partner.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They automatically converge on lexical choices during object naming tasks (e.g., whether to use couch or sofa to name a piece of furniture; Brennan & Clark, 1996; Clark & Wilkes-Gibbs, 1986). They are also found to repeat each other’s syntactic structure (e.g., actives vs. passives) when they take turns to describe depicted events (Branigan, Pickering, & Cleland, 2000; Cai, Pickering, & Branigan, 2012). Some other forms of alignment may reflect more strategic efforts to take a shared perspective with a conversational partner.…”
Section: Discussionmentioning
confidence: 98%
“…Research on lexical ambiguity resolution has shown that comprehenders are extremely sensitive to contextual and distributional factors when selecting a meaning for a semantically ambiguous word such as “bark” (Cai & Vigliocco, in press; Twilley & Dixon, 2000; Vitello & Rodd, 2015). The semantic cues present in preceding words play a key role in the disambiguation of ambiguous words within sentences.…”
Section: Introductionmentioning
confidence: 99%
“…A role for context in language processing has long been recognized, with growing attention from researchers in the last decade or so (see reviews in Cai & Vigliocco, 2018 ; Meteyard & Vigliocco, 2018 ; Yee & Thompson-Schill, 2016 ). It is however the case that most current work still focuses on a single contextual factor.…”
Section: Non-arbitrariness In Language Processingmentioning
confidence: 99%
“…A role for context in language processing has long been recognized, with growing attention from researchers in the last decade or so (see reviews in Cai & Vigliocco, 2018;Meteyard & Vigliocco, 2018;Yee & Thompson-Schill, 2016). It is however the case that most current work still focuses on a single contextual factor.…”
Section: Non-arbitrariness In Language Processingmentioning
confidence: 99%